Steric control in pd-mediated cycloisomerization of sugar alkynols: documentation of a rare allylic epimerization - Ramana, Chepuri V.; Patel, Pitarnbar; Gonnade, Rajesh G. (Tetrahedron Letters, 2007)
Pd-mediated cycloisomerization of C3-alkynylated glucofuranosyl derivatives revealed a dominance of steric factors over electronic factors. However, the intermediate glycals were epimerized prior to the ketalization and afforded the more stable cis-fused bicyclic ketals. (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: Bis-Homopropargylic Alcohols; Oriented Organic-Synthesis; Nucleophilic-Attack; Room-Temperature; Palladium; Chemistry; Heterocycles; Complexes; Transformations; Sonogashira